The origins, growth and future of greater Cape Town : an examination of the response in urban form and structure to the influence of movement in urban development with particular reference to the present and future role of the public passenger transp - Brice, Trevor Edmund (School of Architecture, Planning and Geomatics, 2014)
Bibliography: p. 230-231.